2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27476
|View full text |Cite
|
Sign up to set email alerts
|

A Measure of Affect toward Key Elements of Engineering Professional Practice

Abstract: She received her BS in Bioengineering from Clemson University where she tutored undergraduate mathematics and science courses, and mentored undergraduate engineering majors. Prior to coming to UT, she independently tutored K12 and undergraduate mathematics and science. Her research interests include engineering education, identity and equity. Address: Engineering Training Center II (ETC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…As part of a larger project (Patrick et al 2017), we surveyed over 3000 undergraduate engineering students about their engineering attitudinal beliefs from the fall of 2016 to the spring of 2019. The online survey, which took approximately fifteen minutes to complete, was administered in class during the first 4 weeks of each semester.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As part of a larger project (Patrick et al 2017), we surveyed over 3000 undergraduate engineering students about their engineering attitudinal beliefs from the fall of 2016 to the spring of 2019. The online survey, which took approximately fifteen minutes to complete, was administered in class during the first 4 weeks of each semester.…”
Section: Methodsmentioning
confidence: 99%
“…During its 3-year administration, the survey evolved through several iterations. In all, the instrument captured information about 25 unique factors, several of which are explored in our prior work (e.g., Patrick et al 2017). However, a core set of engineering attitudes were measured consistently at every time point, given their relationships to other academic and professional outcomes.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Similarly, engineering graduate students indicated that communication skills competence is an important aspect for engineers (Choe & Borrego, ). Prior work has developed a scale to measure affect toward professional aspects of engineering identity among undergraduates (Patrick et al, ) and found that this professional scale explained an additional 18% of engineering identity over models considering only engineering performance/competence, interest and recognition (Choe et al, ). While interpersonal skills are only one aspect of professional skills, this prior result is compelling support for including interpersonal skills in a model of graduate engineering identity.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Of these identities, disciplinary engineering identity has been studied most extensively among engineering students. Studies of undergraduate engineering identity have demonstrated relationships between engineering identity and retention in engineering (Patrick et al, ; Pierrakos, Beam, Constantz, Johri, & Anderson, ; Tendhar et al, ) and science and math identity and pursuit of an engineering major (Godwin, Potvin, Hazari, & Lock, ). Other studies are also beginning to link identity to persistence among engineering doctoral students (Miller et al, ).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…We also borrowed items from several constructs to assess engineering graduate student identity including engineering components from undergraduate engineering identity instruments (Patrick et al, 2017;Prybutok et al, 2016 ) and research components from other graduate student instruments (Bieschke, Bishop, & Garcia, 1996). Because original items were not specifically developed for the target population, we interviewed several key informants to provide context on engineering graduate students' experiences as they related to their engineering and research identities.…”
Section: Survey Developmentmentioning
confidence: 99%